PENGARUH LATIHAN LADDER 5HOPS+RUN DAN LATERAL BOX JUMP TERHADAP KELINCAHAN (AGILITY) DAN KECEPATAN (SPEED) - Arif Kustoro; Garnika Ade Sinto Raya (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
Ladder drill is a jump exercise using a ladder. Box jump is an exercise to jump over a box using one or two legs. Both exercises are two improve agility and speed. The target of this research was male students of class XI MAN 1 Gresik, totaling 101 studens. The type of research used is quantitative with quasi-experimental methods. The design of this study uses the non equivalent control-group before-after design, data analysis uses ANOVA. The data collection process was carried out with a hexagon test and 30 meter sprint. Furthermore, the research data were analyzed using the SPSS application series 22.0. The results showed: (1) there was a4significant effect between the ladder 5hop+run training program on an increase in agility by 3.23% and speed by 3.47%; (2) there is4a significant effect between the lateral box jump training program on an increase in agility of 3.71% and speed of 3.17%; (3) there is4a significant effect between the ladder 5hop+run and the lateral box jump training program on increasing agility by 6.94% and speed by 6.64%.